CONSENSUALIDADE NO PROCESSO ADMINISTRATIVO SANCIONADOR DA AGÊNCIA NACIONAL DE ENERGIA ELÉTRICA (ANEEL): UM OLHAR DE RELANCE SOBRE A NOVA FISCALIZAÇÃO ESTRATÉGICA PAUTADA À LUZ DA TEORIA DE REGULAÇÃO RESPONSIVA: a glance at the new Strategic Inspection based on the theory of Responsive Regulation - Lima, Carlos Alberto Ferreira; Lima, Carlos Eduardo Carvalho (Revista da AJURIS, 2023)
CONSENSUALITY IN THE SANCTIONING ADMINISTRATIVE PROCESS OF THE NATIONAL ELECTRIC ENERGY AGENCY (ANEEL): A GLANCE AT THE NEW STRATEGIC INSPECTION BASED ON THE THEORY OF RESPONSIVE REGULATION ÁREA(S): direito administrativo sancionador; regulação responsiva; direito público. RESUMO: O presente artigo faz uma releitura do processo administrativo sancionador da Agência Nacional de Energia Elétrica (“Aneel”), especificamente quanto à possibilidade de ganhos de eficiência pela adoção de mecanismos de consensualidade. A partir da exploração de fontes bibliográficas e da análise de documentos oficiais expedidos pela Aneel, discute-se a transição do modelo de “fiscalização tradicional”, consubstanciada nas ferramentas de comando e controle, com viés bastante punitivo, para a denominada “fiscalização estratégica”, sedimentada à luz da teoria de regulação responsiva, com caráter preventivo, orientativo e educativo da fiscalização. O processo administrativo sancionador deve objetivar, fundamentalmente, o restabelecimento da conformidade regulatória, de maneira menos custosa e mais eficiente, com efetiva melhoria da qualidade na prestação dos serviços públicos de distribuição e transmissão de energia elétrica. ABSTRACT: This article reinterprets the sanctioning administrative process of the National Electric Energy Agency (“ANEEL”), specifically regarding the possibility of efficiency gains through the adoption of consensus mechanisms. Based on the exploration of bibliographic sources and the analysis of official documents issued by ANEEL, the transition from the “Traditional Inspection” model, embodied in command and control tools, with a very punitive bias, to the so-called “Strategic Inspection” is discussed, grounded in the light of the theory of responsive regulation, with a preventive, guiding and educational nature of inspection. The sanctioning administrative process must fundamentally aim at restoring regulatory compliance, in a less costly and more efficient manner, with an effective improvement in the quality of the provision of public electricity distribution and transmission services. PALAVRAS-CHAVE: direito administrativo sancionador; consensualidade; Aneel; fiscalização estratégica; regulação responsiva. KEYWORDS: sanctioning administrative law; consensuality; ANEEL; strategic oversight; responsive regulation. SUMÁRIO: Introdução; 1 Fiscalização e sanção no âmbito da Agência Nacional de Energia Elétrica (“Aneel”): arcabouço legal, regulamentar e demais normatizações aplicáveis à espécie; 2 Fiscalização tradicional dos serviços de eletricidade; 3 Fragilidades do modelo de fiscalização tradicional e necessidade de reforma; 4 Consensualidade no direito administrativo sancionador; 5 Fiscalização estratégica pautada à luz da teoria de regulação responsiva; Conclusão; Referências. SUMMARY: Introduction; 1 Inspection and sanction within the scope of the National Electric Energy Agency (“ANEEL”): legal framework, regulations and other norms applicable to the species; 2 Traditional supervision of electricity services; 3 Fragilities of the traditional inspection model and need for reform; 4 Consensuality in sanctioning administrative law; 5 Strategic supervision based on the theory of responsive regulation; Conclusion; References.